2010
DOI: 10.3746/jfn.2010.15.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Codium fragile Ethanol Extraction Inhibited Inflammatory Response through the Inhibition of JNK Phosphorylation

Abstract: Codium fragile (CF) is an edible green alga consumed as a traditional food source in Korea. In this study, the ethanol extract of CF was evaluated to determine if it has anti-inflammatory activity. Lipopolysaccharide (LPS), a toxin from bacteria, is a potent inducer of inflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6. Therefore, we studied whether CF extracts have an anti-inflammatory effect in LPS-induced murine macrophage cell lines (RAW 264.7). In the present study, IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In recent studies, Codium fragile has been reported to have physiological activities such as anti-obesity as a probiotic, inhibition of food edema inflammation, and skin improvement [ 15 , 16 , 17 ]. In addition, Codium fragile ethanol extract had an anti-inflammatory effect in LPS-induced RAW 264.7 cells [ 18 ]. However, there is little research on Codium fragile between PM 2.5 and the gut–brain axis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, Codium fragile has been reported to have physiological activities such as anti-obesity as a probiotic, inhibition of food edema inflammation, and skin improvement [ 15 , 16 , 17 ]. In addition, Codium fragile ethanol extract had an anti-inflammatory effect in LPS-induced RAW 264.7 cells [ 18 ]. However, there is little research on Codium fragile between PM 2.5 and the gut–brain axis.…”
Section: Introductionmentioning
confidence: 99%